Nucleoside diphosphate kinase B contributes to arrhythmogenesis in human-induced pluripotent stem sell-derived cardiomyocytes from a patient with arrhythmogenic right ventricular cardiomyopathy - Buljubasic, Fanis; El-Battrawy, Ibrahim; Lan, Huan; Lomada, Santosh K.; Chatterjee, Anupriya; Zhao, Zhihan; Li, Xin; Zhong, Rujia; Xu, Qiang; Huang, Mengying; Liao, Zhenxing; Lang, Siegfried; et al. (Journal of Clinical Medicine, 2020)
Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare, inheritable cardiac disorder characterized by ventricular tachyarrhythmias, progressive loss of cardiomyocytes with fibrofatty replacement and sudden cardiac death. The exact underlying mechanisms are unclear. Methods: This study investigated the possible roles of nucleoside diphosphate kinase B (NDPK-B) and SK4 channels in the arrhythmogenesis of ARVC by using human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Results: In hiPSC-CMs from a patient with ARVC, the expression levels of NDPK-B and SK4 channels were upregulated, the cell automaticity was increased and the occurrence rate of arrhythmic events was enhanced. Recombinant NDPK-B applied into hiPSC-CMs from either healthy donors or the patient enhanced SK4 channel current (ISK4), cell automaticity and the occurrence of arrhythmic events, whereas protein histidine phosphatase 1 (PHP-1), a counter actor of NDPK-B, prevented the NDPK-B effect. Application of PHP-1 alone or a SK4 channel blocker also reduced cell automaticity and arrhythmic events. Conclusion: This study demonstrated that the elevated NDPK-B expression, via activating SK4 channels, contributes to arrhythmogenesis in ARVC, and hence, NDPK-B may be a potential therapeutic target for treating arrhythmias in patients with ARVC.
Gesehen am 26.11.2020